2015
DOI: 10.1515/pjs-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Effects of Below-the-Knee Angioplasty in Diabetic Patients with Critical Ischemia of Lower Limbs Referred to Sina Hospital During 2010-2011

Abstract: Despite significant advances in the treatment of diabetic foot ulcers and below-the-knee critical ischemia, there are ongoing efforts to achieve a method with low complication, high success rate and persistence of long-term effects.was to examine the outcome of angioplasty in patients with below-the-knee critical ischemia referred to Hospital.. This semi-experimental study conducted on diabetics patients treated with PTA (Percutaneous transluminal angioplasty) with critical ischemia of lower limbs referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…This was not comparable with Zafarghandi et al, 2015, who found in a study conducted to examine the outcome of angioplasty in patients with below-the-knee critical ischemia that peroneal artery was present in (50%) of patients, (ATA) in (26.92%) of patients, while the (PTA) in (84.61%) patients . [18] Moving to technical success in our study, we find that 92% (36 patients) technically succeeded regarding crossing the lesion, dilatation with residual stenosis less than 30% while failure restricted in two cases due to failure to pass the lesion because of heavy calcification which can be correlated to Conrad et al, 2009, who conducted a study on Infrapopliteal balloon angioplasty for the treatment of chronic occlusive disease, they recorded technical success up to 71.6%. Similarly, Vraux et al, 2000 who evaluated the feasibility and preliminary results at 1 year of angioplasty of tibial occlusions in critical limb ischaemia (CLI) reported a technical success rate of 78% in 40 patients undergoing infrapopliteal PTA for CLI.…”
Section: Mahmoud M; Et Al… -465-supporting
confidence: 68%
See 2 more Smart Citations
“…This was not comparable with Zafarghandi et al, 2015, who found in a study conducted to examine the outcome of angioplasty in patients with below-the-knee critical ischemia that peroneal artery was present in (50%) of patients, (ATA) in (26.92%) of patients, while the (PTA) in (84.61%) patients . [18] Moving to technical success in our study, we find that 92% (36 patients) technically succeeded regarding crossing the lesion, dilatation with residual stenosis less than 30% while failure restricted in two cases due to failure to pass the lesion because of heavy calcification which can be correlated to Conrad et al, 2009, who conducted a study on Infrapopliteal balloon angioplasty for the treatment of chronic occlusive disease, they recorded technical success up to 71.6%. Similarly, Vraux et al, 2000 who evaluated the feasibility and preliminary results at 1 year of angioplasty of tibial occlusions in critical limb ischaemia (CLI) reported a technical success rate of 78% in 40 patients undergoing infrapopliteal PTA for CLI.…”
Section: Mahmoud M; Et Al… -465-supporting
confidence: 68%
“…Similarly, Vraux et al, 2000 who evaluated the feasibility and preliminary results at 1 year of angioplasty of tibial occlusions in critical limb ischaemia (CLI) reported a technical success rate of 78% in 40 patients undergoing infrapopliteal PTA for CLI. , [18] Technical success was lower in patients with TASC D lesions at 50%, compared with 63% as reported previously by Kok et al, 2017 and technical success for the remaining A-C lesions was as higher at 100% as Kok et al, 2017, 81%. [13] After excluding mortality, the overall clinical success, wound healing and limb salvagability in our study was 76.3% while in Conrad et al, 2009 it was 86.2 %.…”
Section: Mahmoud M; Et Al… -465-supporting
confidence: 61%
See 1 more Smart Citation